Successful intravenous immunoglobulin therapy in a case of acute fulminant myocarditis - (:unkn) unknown (My University, 2011)
Fulminant myocarditis is an inflammatory process that occurs in the myocardium and causes acute-onset heart failure. Its prognosis is poor unless patients are promptly and aggressively supported. Although an autoimmune mechanism has been postulated for myocarditis, immunomodulatory treatment strategies are still under investigation. We report on a 30-year-old woman with acute myocarditis, whose condition rapidly deteriorated despite standard medical therapy. High-dose intravenous immunoglobulin therapy (70 g/day for 2 days) was given and the patient showed dramatic improvement on the second day. Left ventricular ejection fraction increased from 32% to 40% and to 50% at 24 and 48 hours of treatment, respectively. She was discharged on the tenth day with normal ejection fraction. She was free of cardiac events during a two-year follow-up. High-dose intravenous immunoglobulin may be potentially useful in selected patients, especially if given early in acute fulminant myocarditis. © 2011 Turkish Society of Cardiology.
Keywords: Cardiomyopathy; Dilated/complications; Heart failure/drug therapy; Immunoglobulins; Intravenous/ therapeutic use; Myocarditis/drug therapy